PROBLEMATIKA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Tijow, Meylani Aljeinie; Sembiring, Desy Anita Karolina; Risamasu, Putri Ellen Gracia; Aryesam, Agnes (Program Studi Manajemen Pendidikan FKIP Universitas Cenderawasih, 2023)
The Covid-19 pandemic resulted in the emergence of accelerated learning that was previously carried out attractively to be courageous in order to suppress the increase in cases of the Covid-19 virus. This study describes what learning problems are faced by students and also lecturers in the Department of Education, Cenderawasih University. The research method used is descriptive quantitative with indicators including, encouraging learning strategies and clarity, quality of learning materials, student involvement and activeness in the brave class (student engagement) and achievement of course learning achievements (CPMK) as a form of evaluating brave learning during the Covid pandemic -19. The results showed that from a student's point of view, learning courage during the Covid-19 pandemic at JIP Cenderawasih University was still not effective and efficient. Some of the reasons behind this are that there are still many students who do not have gadgets as learning media and it is difficult for students to get internet access.